(untitled) (Bangladesh Journal of Microbiology, 2016)
The antimicrobial agents of bacteria isolated from different rhizosphere of fruits and vegetables soil in Lahore. Of ten species, five were gram-negative (Escherichia coli, Pseudomonas fluorescence, Klebsiella pneumoniae, Salmonella typhii, Brachybacterium faecium); other five were gram positive and identified as Bacillus farraginis, Kurthia gibsonii, Aureobacterium liquefaciens, Curtobacterium albidum, Micrococcus lylae. The antagonistic potential of bacterial strains was assessed by the well diffusion technique and results indicating varying degree of biocontrol activity against pathogenic strain of X. campestris. Out of ten bacterial species, E. coli (gram negative) and C. albidum (gram positive) showed a high prevalence of resistance with reduction of 4.2cm and 4.1cm zone diameter respectively. The minimum inhibitory volume (MIV) to two bio-agents was determined for X. campestris from range 10-100 ?L. E. coli (volume required to inhibit < 20 ?L) and C. albidum (volume required to inhibit < 40 ?L) exhibited good activity against pathogen. These results provide information on the prevalence of resistant bacterial strains with the MIV of organisms and indicate the possibility of using these bacterial species as bio-agent against X. campestris. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 37-40